Spaghetti unravelled: a model-based description of differences in income-age trajectories - Stephen P. Jenkins (University of Essex, Institute for Social and Economic Research (ISER), 2009)
A modelling framework is developed for describing income-age trajectories that is useful for summarizing not only the average profile for a group of individuals with similar characteristics, but also how individual trajectories differ from the group average. Using data from waves 1-17 of the British Household Panel Survey, the model is estimated separately for twelve groups of individuals differentiated in terms of educational qualifications, birth cohort and sex. The results indicate significant differences in the shapes of average trajectories across groups, and substantial variations in trajectories across individuals within groups.
Keywords: 330